The role of pulse repetition rate on picosecond pulsed laser processing of Zn and Zn-coated steel. (November 2020) - Mustafa, H.; Matthews, D.T.A.; Römer, G.R.B.E.
Highlights: MRR is defined by pulse energy and number of pulses than average power. MRR increases for heat accumulation and ablated depth decreases for particle shielding. Heat accumulation is higher in bulk zinc than in Zn-coated sample. Steel substrate acts as a heat sink inhibiting a higher degree of heat accumulation. Abstract: Zinc and zinc-coated steel is processed with a picosecond laser source at a wavelength of 1030 and 515 nm to investigate the effect of time between consecutive pulses, i.e. pulse repetition rate on the laser ablation efficiency, in terms of maximum achievable depth of the ablated crater, material removal rate and processing quality. With increasing pulse repetition rate up to 40 kHz and number of pulses on the same location, material removal rate increases due to heat accumulation, while the maximum achievable depth decreases due to particle shielding for both zinc and zinc coated steel. It was found that, unlike the zinc-coated sample, both material removal rate and achievable depth is enhanced for bulk zinc at high repetition rates, due to a greater degree of heat accumulation than particle shielding. Using a numerical heat flow model, it is shown that the difference between bulk zinc and zinc-coated steel stems from the steel substrate that effectively acts as a heat sink for the absorbed energy in the zinc coating, inhibiting a higher degree of heat accumulation.